Infografis : Kedasyatan cara bercerita visual / Jason Lankow, Josh Ritchie, dan Ross Crooks; Penerjemah, Alex Tri Kantjono Widodo - LANKOW, Jason; RITCHIE, Josh; CROOKS Ross; ALEX Tri Kantjono Widodo (Gramedia Pustaka Utama, 2014)
253 hlm. : ilus. ; 23 cm.